PENGARUH PENGGUNAAN TEKNIK COPY THE MASTER TERHADAP KETERAMPILAN MENULIS TEKS EKSPOSISI SISWA KELAS VIII SMP NEGERI 5 PARIAMAN - Putri, Puput Anggraini; Thamsin, Andria Catri (Universitas Negeri Padang, 2019)
ABSTRACT The purpose this research are (1) To find out the exposition text writing skills at class VIII SMP at 5 Pariaman before using copy the master technique. (2) To find out the exposition text writing skills ot class VIII SMP at 5 Pariaman after using copy the master technique. (3) To analyze the effects of using copy the master technique towards the exposition text writing skills at class VIII SMP at 5 Pariaman. This is quantitative research using quasi experiment. Based on data analysis, using copy the master technique affects to students class VIII SMP at 5 Pariaman the exposition text writing skills. Kata kunci: Pengaruh, Teknik Copy The Master, Menulis Teks Eksposisi